PENGGUNAAN MEDIA PEMBELAJARAN PUBG (POP UP BOOK GAYA) DALAM UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA PADA PEMBELAJARAN IPA KELAS 4 SDN DALANGAN: POP UP BOOK GAYA (PUBG) - Fania Nova Emalia Fania; Makhrifat; Finda Wulan Sari; Danuri (LPPM Universitas Cipta Mandiri, 2024)
This research aims to see whether there is an influence on the learning achievement of class IV students at SDN Dalangan on the science subject style material which is influenced by the use of the pop up book style learning media compared with the results of student learning achievement if they do not use the pop up book style. The population in this study was all 22 students in class IV of SDN Dalangan. This research uses a quantitative type of research with a pretest posttest control group research design. The data collection technique uses saturated samples. The data collection technique uses a pretest and posttest, each consisting of 25 multiple choice questions. So from this research there is a difference in learning achievement in science subject style material between those who use PUBG (Pop Up Book Gaya) learning media and those who do not use PUBG media (Pop Up Book Gaya).